133k views
4 votes
Derive the quadratic formula from the standard form (ax² + bx + c = 0) of a quadratic equation by

following the steps below.
1. Divide all terms in the equation by a.
2. Subtract the constant (the term without an x) from both sides.
3. Add a constant (in terms of a and b) that will complete the square.
4. Take the square root of both sides of the equation.
5. Solve for x.​

1 Answer

7 votes

1. Divide all terms by a:


x^(2)+(b)/(a)x +(c)/(a) =0

2. Subtract the constant (which is c/a):


x^(2) +(b)/(a)x =-(c)/(a)

3. Complete the square, then add the constant to both sides:


(x+(b)/(2a))^(2) - (b^(2) )/(4a^(2)) =-(c)/(a) (now add the constant in terms of a and b)


(x+(b)/(2a))^(2) = -(c)/(a) +(b^(2))/(4a^(2)) (now simplify the fractions on the right side)


(x+(b)/(2a))^(2)= (-c(4a)+b^(2))/(4a^(2))


(x+(b)/(2a))^(2)= (-4ac+b^(2))/(4a^(2)) (now just put the b^2 in front)


(x+(b)/(2a))^(2)= (b^(2)-4ac)/(4a^(2))

4. Square root both sides and simplify the right side:


x+(b)/(2a) = \sqrt{(b^(2)-4ac)/(4a^(2)) } (you can square root the bottom bit of the fraction fully)


x+(b)/(2a) = \frac{\sqrt{b^(2)-4ac} }{2a}

5. Now just solve for x:


x= (√(b^2-4ac))/(2a)-(b)/(2a) (now simplify)


x=\frac{-b+\sqrt{b^(2)-4ac}}{2a} (note: it should be a plus or minus sign infront of the squareroot, not just a plus sign -it's just that i can't write it in )

_____________________________

If you have any questions, feel free to ask.

User Sven Lilienthal
by
4.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.